Understanding the HDP Nexus - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
This carousel explains the Humanitarian–Development–Peace (HDP) Nexus and why it matters for working in fragile and crisis-affected contexts. It starts by showing how humanitarian aid, development programs, and peace efforts have often responded to the same crises separately, leading to gaps, duplication, and missed opportunities. Using examples like drought and food insecurity in the Horn of Africa, it illustrates why short-term relief alone is not enough. The carousel then introduces the HDP Nexus as a way of working that connects emergency response, long-term resilience, and peacebuilding so they reinforce each other. It highlights the benefits of better coordination, early action, and shared data, while also acknowledging the real challenges of aligning funding, systems, and priorities across sectors